AN INDIAN POET CONTEMPLATES ON THE LIFE OF JESUS CHRIST : A CRITICAL APPRECIATION OF THE KRISTUBHAGAVATA OF PROF. P.C. DEVASSIA - Thottakara, Augustine (Journal of Dharma, 2002)
Jesus Christ is an Asian. He was born in Asia; he lived his thirtythree years of embodied existence, preached his message of love and salvation, died on the Cross and resurrected to life again in the Asian soil. All the world religions, in fact, took origin and grew strong in Asia. Hinduism, Judaism, Zoroastrianism, Jainism, Buddhism, Confucianism, Taoism, Shintoism, Islam and Sikhism: all these are products of Asia. No other continent, I presume, can claim to be the birth place of a world religion, with written foundational sacred texts, organized and systematized liturgical worship, precisely prescribed belief system, a definite founder whose inner spiritual experience gives the inspiration and basis to a particular religious tradition, and defined doctrines concerning the ultimate eschatological good of human existence. One may argue that some of the above-mentioned systems are not proper religions, but are only ways of life with a well-defined- moral code and time-tested principles for orderly societal life